How many species of Sturisoma (Siluriformes: Loricariinae) inhabit the La Plata Basin? - Cardoso, Yamila; Bogan, Sergio; Agnolin, Federico; Petean, Flávia De Figueiredo (Zootaxa, 2023)
The aim of the present contribution is to review the taxonomy of the loricariid Sturisoma in the La Plata basin. The original description of the species S. barbatum is analyzed and compared to Regan’s later description of S. robustum. We noticed that Kner’s illustrations may have influenced the description by Regan and other later authors, leading to confusion in the taxonomy of Sturisoma. The diagnostic characteristics and molecular data of S. barbatum and S. robustum are discussed, and we concluded that the differences observed by previous authors are part of the intraspecific variation within a single species. This indicates that S. barbatum is a senior synonym of S. robustum. Sturisoma barbatum is compared to other Sturisoma species.